2013
DOI: 10.1016/j.freeradbiomed.2013.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage to macromolecules in human Parkinson disease and the rotenone model

Abstract: Parkinson’s disease (PD), the most common neurodegenerative movement disorder, is associated with selective degeneration of nigrostriatal dopamine neurons. While the underlying mechanisms contributing to neurodegeneration in PD appear to be multifactorial, mitochondrial impairment and oxidative stress are widely considered to be central to many forms of the disease. Whether oxidative stress is a cause or consequence of dopaminergic death, there is substantial evidence for oxidative stress in both human PD pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
210
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(216 citation statements)
references
References 178 publications
(197 reference statements)
6
210
0
Order By: Relevance
“…In this context, previous studies showed that ROT could impair antioxidant enzyme activity in the brain of rats and induce Parkinson disease (28,29). Another study reported that ROT by ROS generation induced cell apoptosis (30).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this context, previous studies showed that ROT could impair antioxidant enzyme activity in the brain of rats and induce Parkinson disease (28,29). Another study reported that ROT by ROS generation induced cell apoptosis (30).…”
Section: Discussionmentioning
confidence: 94%
“…Exposure to ROT causes enhancement of LPO and antioxidant status impairment in human and animal tissue (28).…”
Section: Discussionmentioning
confidence: 99%
“…Increased protein modification by the reactive lipid peroxidation product 4-hydroxy-2-nonenal (HNE) has been described in neurodegenerative diseases (35)(36)(37). Several mitochondrial enzymes, including the pyruvate dehydrogenase, ␣-ketoglutarate dehydrogenase and branched-chain ␣-keto acid dehydrogenase complexes are targets of HNE conjugation (38).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, markers of oxidative damage in PD patients were also detected in the serum and urine [132][133][134][135], but their use as indicators of the course of the disease is far from being useful for clinical practice because the existing data are contradictory [136][137][138]. As has been suggested [136][137][138], these differences may be due to the variability in methods used to measure OS markers.…”
Section: Clinical Studies Oxidative Biomarkersmentioning
confidence: 99%